Characterization of Thermal Waters Origin from the Back Arc Lampung Province, Indonesia: An Evaluation of Stable Isotopes, Major Elements, and Li/Cl Ratios - Mochamad Iqbal; Brenda Ariesty Kusumasari; Tedi Atmapradhana; Afi Candra Trinugraha; Endah Kinarya Palupi; Ikhsan Maulidi (CV FOUNDAE, 2023)
This study reports chemical and isotope data from thermal water samples collected in the Natar area (back-arc Lampung province), Indonesia. Based on the geologic map, Lampung-Panjang Fault is the source of this thermal water appearance with Quaternary volcanic and metamorphic rock in the basement. It is located close to the Quaternary extinct volcano (Mount Betung) around 20 km to the southwest. Therefore, this study aims to provide information on geochemical characteristics and the origin of thermal waters in Natar's non-volcanic area. Variables such as stable isotopes, major, and Li/Cl ratios were analyzed. Furthermore, the thermal waters collected from a well in a different location have a moderate temperature ranging from 47°C to 54°C with 6.23 pH. Lithium and Chloride concentrations as well as Isotope δ18O and δD ranges from 0.02 mg/L to 0.04 mg/L, 5.19 mg/L to 46.12 mg/L, -5.26 ‰ to -2.65 ‰, and -5.26 ‰ to -2.65 ‰, respectively. The stable isotope showed that the thermal water samples have a shift value of ó18O similar to hydrothermal water. The result also has a positive correlation with the distribution of the Li/Cl ratio plotted close to the magmatic water. Consequently, the Natar hot springs may have formed due to the magmatic process of Mount Betung Quaternary with a lower temperature than an active volcano.